Analisis Komunikasi Cuitan Paus Fransiskus pada Akun X @Pontifex dalam Perspektif Servant Leadership - Handayani, Lusia Sri; Isnaini, Muhamad (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2025)
The purpose of this study is to describe the construction of tweets on the X @Pontifex account (January to April 2025), to describe Van Dijk's critical discourse analysis of Pope Francis' tweets (posts) on the X @Pontifex account. This study is a qualitative study using the critical discourse analysis method of the Teun A. Van Dijk model. The results of the study show that Pope Francis' servant leadership has the following characteristics: listening, teaching, empathy, healing, awareness, persuasion, conceptualization, futuristic, management, commitment, and building community. Macrostructure is related to the topic: gratitude, brotherhood, peace, exemplary, service, love, forgiveness, repentance, humanity, diplomacy of truth, forgiveness, freedom and justice. Superstructure is done by placing it at the beginning of the paragraph as an emphasis. Microstructure includes semantics, syntax, stylistics and rhetoric. Semantically, the meaning is conveyed explicitly or directly. Through @Pontifex, Pope Francis calls for peace and the values ​​of life. As a spiritual leader, the Pope integrates technology in carrying out his ministry duties. This inspires leaders that spiritual leadership, servant leadership are synergistic with leadership in the digital era.